Contribution of workers' remittances to economic growth in Pakistan: exploring the role of financial sector development. (2nd January 2016) - Luqman, Muhammad; Haq, Mirajul
Abstract : Since overseas workers' remittances are the most important source of foreign exchange earnings in Pakistan, their contribution to economic growth has not been rigorously analysed. In this study, we attempt to investigate whether a country's absorption capacity affects remittances' response to economic growth or not. The absorption capacity is confined to the development of local financial sector that comprises three different components of financial development. The index of financial sector development is constructed through principal components analysis. To test our hypothesis, we used the autoregressive distributed lag-bound testing approach of co-integration, which is based on time-series data over the period from 1972 to 2011. Our empirical findings validate the hypothesis that the local financial sector development enhances the contribution of overseas workers' remittances to economic growth in Pakistan.